TASKS OF CLOUD TECHNOLOGIES AS A TOOL IN THE DEVELOPMENT OF DIGITAL COMPETENCES - Mamarajabov Odil Elmurzaevich (Scholar Express Journal, 2024)
In the development of the digital environment, the individual is used to search, analyze and use resources from it. Therefore, it is important to use cloud technologies of digital content and to prepare future teachers to operate in the digital economy and to increase the digital literacy of the entire generation.
Keywords: Virtuality; Professional cooperativeness; Infatuation